2011
DOI: 10.1002/alr.20088
|View full text |Cite
|
Sign up to set email alerts
|

Oral antifungal therapy for chronic rhinosinusitis and its subtypes: a systematic review

Abstract: The composite data suggests a potential beneficial effect of oral itraconazole and ketoconazole in patients with CRS and its subtypes. However, majority of the studies are uncontrolled case series, confounded by non-validated outcome variables. Randomized controlled trials are required to better elucidate their role in CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In a recent meta-analysis including 6 randomized controlled trials in CRS patients, evidence was against the effectiveness of either topical or systemic antifungal therapy 31 . However, in a select subgroup of AFRS patients, oral itraconazole and ketoconazole had a more positive response, although most of these studies were uncontrolled 32 . Oral itraconazole yielded positive effects in a subset of asthmatic patients with fungal sensitivity 10 and the majority of asthma or ABPA patients that cannot tolerate itraconazole appear to benefit from either posaconazole or voriconazole 11 .…”
Section: Discussionmentioning
confidence: 97%
“…In a recent meta-analysis including 6 randomized controlled trials in CRS patients, evidence was against the effectiveness of either topical or systemic antifungal therapy 31 . However, in a select subgroup of AFRS patients, oral itraconazole and ketoconazole had a more positive response, although most of these studies were uncontrolled 32 . Oral itraconazole yielded positive effects in a subset of asthmatic patients with fungal sensitivity 10 and the majority of asthma or ABPA patients that cannot tolerate itraconazole appear to benefit from either posaconazole or voriconazole 11 .…”
Section: Discussionmentioning
confidence: 97%
“…275,283,284 There is also the potential for inducing fungal resistance due to the low concentrations used in topical formulations. Multiple trials used concentrations of amphotericin B at 100 µg/mL, a concentration that has been documented to not impede fungal growth in vitro compared with true inhibition at 200 and 300 µg/mL.…”
Section: Role Of Fungi In Crsmentioning
confidence: 99%
“…Every systematic review that was limited to RCTs 255,258,275 concluded that there was no beneficial effect from either oral or topical antifungal therapy in CRS. The only potential benefits of oral antifungal therapies were found in a systematic review of observational studies with nonvalidated outcome measures, 283 which carry a risk of bias that makes conclusions impossible. In the Cochrane review, 275 which included both oral and topical antifungals and had strict inclusion criteria, there was no evidence of benefit for topical antifungals.…”
Section: Rhinosinusitis Guideline Evidence-based Statementsmentioning
confidence: 99%
“…Given the hepatotoxic effects and potential cardiotoxic effects of the medication and its cost, as well as our inability to predict the small subset who will respond, itraconazole should be utilized sparingly and usually as a last resort. A review of the literature on oral antifungal therapy in the treatment of CRS was performed in 2011 and suggested some potential benefi t from using itraconazole and ketoconazole, but the level of evidence was low [ 21 ].…”
Section: Systemic Antifungalsmentioning
confidence: 99%